Growth and nutritional content of Pleurotus ostreatus using different substrates (rice straw, vermicompost and vermiwash) - Singh, Surujanie; Diana, Seecharran; Ansari, Abdullah Adil (Mushroom Research, 2021)
Vermiculture is a significant part of sustainable agriculture and organic farming techniques that lead to a decrease in organic materials through practicing vermitechnology which includes vermicomposting and vermiwash. Vermicompost and vermiwash can be used as suitable substrates for cultivation of nutritious edible mushrooms. Mushrooms acts as decomposers in the environment by degrading complex organic materials or any type of lignocelluloses substrates in plants and animals. The study investigated the growth and nutritional content of oyster mushrooms (Pleurotus ostreatus) using different types of substrates. Pleurotus ostreatus showed significant growth when subjected to five treatments of vermicompost, vermiwash and rice straw (in different combinations) compared to control substrate. Among the different treatments, there was no significant effect of the fresh (p =0.469) and dry weight (p =0.385). The results showed that the vermicompost (T2) was the best substrate with a yield of 215.75g and 22.01g for fresh and dry weight respectively, producing mushrooms with significantly better growth parameters. Vermicompost and vermiwash, rice straw, vermiwash substrates can be effective for the growth of oyster mushrooms.